Description of Campylobacter curvus and C. curvus-Like Strains Associated with Sporadic Episodes of Bloody Gastroenteritis and Brainerd's Diarrhea - Abbott, Sharon L. (American Society for Microbiology, 2005)
Campylobacter curvus is a rarely encountered Campylobacter species in human, animal, and environmental samples. During the course of two investigations, one involving a search for possible bacterial agents causing bloody gastroenteritis and a second concerning a small outbreak of Brainerd's diarrhea in northern California, 20 strains of C. curvus or C. curvus-like organisms were isolated by a microfiltration technique and prolonged incubation. The results suggest that C. curvus may be an underappreciated Campylobacter that may be involved in sporadic and outbreak cases of bloody or chronic diarrhea in humans.